Lethal effects of insecticides on adults of Eriopis connexa (Germar, 1824) (Coleoptera: Coccinellidae) - Pasini, Rafael A.; Rakes, Matheus; De Armas, Franciele S.; Pazini, Juliano de B.; Grützmacher, Anderson D. (Entomological Communications, 2022)
The predator Eriopis connexa (Germar, 1824) (Coleoptera: Coccinelidae), is an important biological control agent in wheat fields. In this work, we evaluated the lethal effects of fifteen insecticides used in the wheat crop on adults of the predator E. connexa, using the methodology proposed by International Organization for Biological and Integrated Control (IOBC). Sublethal effects have not been evaluated. The insecticides were sprayed on glass plates that were used to set up the exposure arenas. The chitin synthesis inhibitors diflubenzuron SC, diflubenzuron WP, lufenuron, triflumuron, and the pyrethroid beta-cyfluthrin were considered harmless to adults of the predator and should have their use prioritized. On the other hand, methomyl, lambda-cyhalothrin, thiamethoxam + lambda-cyhalothrin A and B were considered harmful to E. connexa and should be avoided when adults of the predator are present in the crop.